Thrifting sebagai Tren Sosial: Kajian Komunikasi Islam - Maghrobi, Najwa Aula (Journal of Islamic Communication Studies, 2025)
Thrifting, or the consumption of secondhand clothing, has become a significant social trend among Generation Z. This study aims to analyze the perceptions of Gen Z Communication Studies students at UIN Sunan Ampel Surabaya regarding secondhand clothing consumption through three indicators of perception: attention, evaluation, and response. A descriptive qualitative method was applied using in-depth interviews with ten informants. The results show that students’ attention toward thrifting is primarily driven by exposure to social media content (TikTok and Instagram) featuring thrift hauls at affordable prices, influenced by the FOMO (Fear of Missing Out) phenomenon. In the evaluation stage, students view thrifting as a multidimensional activity that is not only economically efficient but also serves as a medium for self-expression and a part of social trends. In the response stage, students demonstrate positive attitudes with purchase intensity adjusted to their needs, motivated by confidence in appearing unique and different. The study concludes that students’ perceptions of secondhand clothing consumption have evolved from being a low-cost alternative to a strategic consumption practice for expressing identity and lifestyle among Gen Z. From the perspective of Islamic communication, thrifting reflects a simple and ethical consumption behavior that rejects isrāf (extravagance) and tabdzīr (wastefulness) in accordance with Islamic values.